Gambaran Kepatuhan Minum Obat Pada Pasien Hipertensi di Salah Satu Puskesmas Semarang Barat Jawa Tengah - Dewi, Rissa Maharani; Widiya , Hartika; Farizi , Gilang Rizki Al (Journal of Pharmaceutical and Sciences, 2025)
Introduction: Hypertension is a medical condition characterised by blood pressure that is higher than usual and persistent. Based on previous studies, it was found that the low level of compliance in taking medication was related to a decrease in the quality of life for hypertensive patients. This study aimed to determine the compliance of hypertensive patients with taking medicines at one of the West Semarang Community Health Centres, Central Java. Methods: Analytic descriptive research. This type of research is observational with cross-sectional techniques, with respondents being hypertensive patients at one of the Puskesmas in West Semarang, Central Java, in 2023. Data analysis was conducted by looking at whether or not drug compliance affected patient characteristics using the chi-square Morisky Medication Adherence Scale 8 (MMAS-8) test. Results: female gender is higher than male, age 36 years to 45 years and 56 years to 65 years have high adherence, diploma and undergraduate education have high adherence values, occupation of housewives and civil servants / TNI / POLRI have high adherence to taking medication and long suffering above 2 years of moderate drug compliance, hypertension therapy with 2 to 3 drugs moderate adherence rather than one drug, other disease characteristics are equally high in adherence.Conclusion: Adherence to the use of antihypertensive medications in one Puskesmas in West Semarang, Central Java, was in the high and medium categories. Men have a moderate adherence category, and women have a high adherence category.